Motion planning of sensorless differential drive mobile robot using clothoid - Zakaria, W. Z. E. W.; Ramli, A. L. A.; Reif, U. (Mathematical Modeling and Computing, 2025)
Mobile robots have the ability to navigate safely and cost-effectively from one location to another. In sensorless motion planning, the absence of sensor data poses challenges for continuous replanning to ensure that the robot follows the desired trajectory. Our research addresses this gap by leveraging computational methods for curve generation within the domain of Computer-Aided Geometric Design (CAGD). Specifically, we propose a clothoid-based, sensorless motion planning algorithm for differential drive mobile robots, assuming the known initial point, end point, and initial direction. Differential drive mobile robots, commonly used in various vehicles and robotics applications, are valued for their reliability and ease of use. These robots control movement through differential speed adjustments between the left and right wheels, with curvature determining the respective wheel speeds. In this paper, we detail the process of generating the clothoid curve and connecting it across two or more points, ensuring that each consecutive clothoid follows the direction in which the previous clothoid ends. We also present simulation results to assess the effectiveness of the proposed technique. The curve formulation and computational approach are tailored to this specific problem, utilizing MATLAB's Remote API capabilities and CoppeliaSim's robot simulation software for implementation.